2021
DOI: 10.1002/jcop.22527
|View full text |Cite
|
Sign up to set email alerts
|

“The worst time of my life”: Treatment‐related stress and unmet needs of women living with infertility

Abstract: Approximately 12% of women in the United States have difficulty getting pregnant or carrying a pregnancy to term (i.e., infertility). Infertility permeates women's lives and is psychologically, socially and financially burdensome. This study aimed to describe women's experiences regarding infertility and explore factors that women find helpful to alleviate their fertility-related stressors. Using purposive sample, we conducted in-depth qualitative interviews with infertile women. Participants reported multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Infertility has been recognized as a worldwide public health problem by the World Health Organization (WHO), and approximately half of these cases lack an definitive explanation for pregnancy failure 3 . It is estimated that in western countries, one in six couples has infertility, which is recognized as the cause of psychological distress in both men and women 4 . In vitro fertilization (IVF) offers a possibility for achieving pregnancy, but the success rate is still suboptimal 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Infertility has been recognized as a worldwide public health problem by the World Health Organization (WHO), and approximately half of these cases lack an definitive explanation for pregnancy failure 3 . It is estimated that in western countries, one in six couples has infertility, which is recognized as the cause of psychological distress in both men and women 4 . In vitro fertilization (IVF) offers a possibility for achieving pregnancy, but the success rate is still suboptimal 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…White women with higher education and higher income had more access to treatment. Öztürk et al, 2021 [ 70 ] Cross-sectional analysis, qualitative study Single institution n = 12 2018 Infertility treatment Income, rural/under-resourced All study participants reported increased financial strain due to treatment costs. Some patients considered the financial burden of treatment to be more stressful than the treatment itself.…”
Section: Resultsmentioning
confidence: 99%
“…To solve their infertility problems, more than half of infertile couples seek medical care like assisted reproductive technology (ART) treatments ( Boivin et al, 2007 ). ART treatments constitute an additional source of stress for infertile couples due to expensive, time-consuming, invasive, and physically demanding procedures, along with the uncertainty of the outcomes ( Öztürk et al, 2021b ). Indeed, infertile patients, and especially women, report that ART treatments are physically and emotionally exhausting ( Arya and Dibb, 2016 ; Anaman-Torgbor et al, 2021 ; Öztürk et al, 2021b ), which is a major cause of premature treatment discontinuation by 30% of couples ( Pedro et al, 2017 ; Domar et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…ART treatments constitute an additional source of stress for infertile couples due to expensive, time-consuming, invasive, and physically demanding procedures, along with the uncertainty of the outcomes ( Öztürk et al, 2021b ). Indeed, infertile patients, and especially women, report that ART treatments are physically and emotionally exhausting ( Arya and Dibb, 2016 ; Anaman-Torgbor et al, 2021 ; Öztürk et al, 2021b ), which is a major cause of premature treatment discontinuation by 30% of couples ( Pedro et al, 2017 ; Domar et al, 2018 ). Altogether, the specific stress associated with infertility and its treatment can have long-lasting psychosocial consequences on infertile individuals and couples ( Schmidt, 2009 ).…”
Section: Introductionmentioning
confidence: 99%